Qualidade de vida relacionada à saúde em mães de crianças e adolescentes portadores de síndrome de Down - Rocha Júnior, Luiz Duarte de Ulhôa (2010)
The present study has the objective of evaluating the HRQL of mothers of children and adolescents affected by DS in comparison with mothers of healthy children and adolescents and verify the association with clinical and demographical variables and with the HRQL of the affected, as perceived by their mothers. Participated in this study mothers of subjects affected with DS and mothers of healthy subjects with maximum age of 21 years, paired by gender and age of the affected subjects in reason of 2:1. After signing the free and clear term, the mothers answered a questionnaire with their demographical information (age, conjugal situation, scholarity, paid activities, family income) and their children information (age, gender, number of brothers, scholarity); and also clinical data about the mother (presence of chronical disease), about the children with DS (use of medication, presence of other chronical diseases or comorbities) and about the family (other people affected by chronical disease in the same residence). The HRQL of the mothers was evaluated through the Medical Outcomes Survey Short Form36 (SF-36) and the intensity of the depressive symptons was verified through the Beck s Depression Inventory (BDI). The mothers of subjects affected with DS with age 5 of greater also answered the Child Health Questionnaire Parental Form 50 (CHQ-PF50), to evaluate the QVRS of the affected, and to the Child Assestment Questionnaire (CHAQ), to evaluate the functional capacity. The Alfa Cronbach coefficient was calculated to determine the reliability of the instruments. The SF-36 scores were compared between the control group and the group of mothers of children affected with DS (Mann-Whitney test). The demographical and clinical variables were compared (Mann-Whitney test, Kruskal-Wallis or Qui-Square) and correlated (Spearman s correlation coefficient) with the scores of the SF-36. The medium age of the mothers in the DS group was 39.0 years and in the control group it was 35.0 years. In relation with the subjects with DS, most of them were males (61.0%), their medium age was 8.0 years, with predominance of adolescents (41,7%). The Alpha-Cronbach coefficient varied from 0.75 to 0.94 to the SF-36. The mothers of subjects affected by DS obtained significantly lower scores than the mothers of the control group in the following domains: physical function, general health, vitality, social function and mental component summary in the SF-36 (p<0,05). The CHQ-PF50 scales that were mostly correlated with the scores of the SF-36 were: behavior, mental health and health perception. Concluding, mothers of subjects affected with DS presented negative impact in the mental dimension, in comparison with the mothers of healthy children and adolescents. The greater the intensity of the depressive symptoms, the greater was the physical and mental injury in the HRQL of the mothers. Few associations were found between the other demographical and clinical variables that were analyzed.